THE EFFICIENCY EVALUATION OF TAEKWONDO COACHES - Njegovan, Jovana (Sport - nauka i praksa, 2024)
The aim of this research was to explore the level of agreement between athletes and taekwondo coaches regarding their efficiency, as well as to investigate the deeper meaning behind coaches' responses regarding their preparation methods for regular training sessions and collaboration with other coaches. The research sample included ten coaches from the Taekwondo Association of Bosnia and Herzegovina and 265 taekwondo athletes. A quantitative-qualitative research approach was employed. In the quantitative part, research instruments such as a questionnaire for coaches and a five-point Likert scale were used for the assessment and self-assessment of taekwondo coaches' professionalism, along with an interview protocol for coaches. The qualitative part of the research utilized in-depth interview techniques. In line with specific research questions and qualitative coding methods, two areas and four categories with corresponding dimensions of taekwondo coaches' efficiency were identified in the final version of the codebook. The analysis of the obtained results suggests a positive assessment and self-assessment of taekwondo coaches' efficiency, with no significant difference between athletes' assessments and coaches' self-assessments of the given factor. In the qualitative part of the research, insights from coaches' responses revealed that the majority of coaches are efficient and dedicated in their coaching endeavours.
Keywords: competence analysis; martial arts; coaches